Strategies of Early Childhood Teachers in Implementing the Pancasila Student Profile through Differentiated Learning: A Case Study - Fitriani, Dewi; Zulfikar, Teuku; Habiburrahim, Habiburrahim (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – The COVID-19 pandemic has led to noticeable behavioural changes and negative character traits among Indonesian children, as evidenced by a decline in the national student character index. The Pancasila student profile, a framework for character and competency development within Indonesia's Merdeka Curriculum, aims to address these challenges. This study examines how the Pancasila student profile is implemented through differentiated learning in Early Childhood Education (ECE) Penggerak Schools in Banda Aceh, providing insights into effective strategies for holistic child development.Design/methods/approach – This qualitative case study was conducted in two ECE institutions (one public, one private) participating in the Penggerak School Program. Data were collected through interviews with two kindergarten teachers, classroom observations, and document analysis. Thematic analysis was applied to identify key implementation strategies.Findings – The study revealed six key strategies for integrating the Pancasila Student Profile into ECE Penggerak schools through differentiated learning: (1) internalizing Islamic values in learning materials, (2) fostering child-led activity choices, (3) employing diverse teaching methods, (4) utilizing varied learning media, (5) engaging parents and the community (Tri-Sentra Pendidikan), and (6) adapting project-based learning flow to school contexts.Research implications/limitations – While the study provides valuable insights, its findings are limited to two schools in Banda Aceh, restricting generalizability. The short duration (two weeks) and reliance on teacher perspectives may also affect depth. Future research should expand to diverse regions, incorporate longitudinal designs, and include parent/child viewpoints to strengthen validity.Practical implications – The findings suggest that ECE educators should adopt differentiated learning tailored to children's interests and readiness, strengthen parental involvement, integrate local and digital resources, and flexibly adapt project-based learning to align with school capacities.Originality/value –This study addresses a gap in research on differentiated learning in Indonesian ECE, particularly within the Penggerak school program framework. It offers a practical model for embedding national character values into early childhood curricula, supporting Indonesia's goals for holistic student development.Paper type Case Study